PENGARUH PEMBERIAN BROMELAIN NANAS TERHADAP PENURUNAN INFLAMASI PADA LANSIA PENDERITA RHEUMATOID ARHTRITIS DI PANTI JOMPO YAYASAN GUNA BUDI BAKTI MEDAN TAHUN 2018 - eva latifah nurhayati (Universitas Prima Indonesia, 2018)
In society, it is often found that Rheumatoid Arthritis causes symptoms of fatigue, joint pain and stiffness. Rheumatoid Arthritis is an autoimmune disease in which the joints (usually the joints of the hands and feet) experience inflammation, causing swelling, pain and often eventually causing damage to the inside of the joint. This study aims to determine the effect of bromelain pineapple on the reduction of inflammation in patients with Rheumatoid Arthritis in Nursing Home Medan Guna Budi Bakti Foundation 2018. This type of research is pre-experimental research using Wilcoxon test. The population of all elderly people with rheumatoid arthritis and the study sample was the entire population. The sampling technique in this study was taken using the total sampling method. The results of the final research using the Wilcoxon test showed that the value of Z = ,3,162 and the value of P-value = 0,002 5 0,05, so there was an effect of giving pineapple bromelain to the reduction of inflammation in elderly people with rheumatoid arthritis in Nursing Homes Medan Guna Budi Bakti Foundation 2018 Conclusion of the research from the researchers that there is an effect of pineapple bromelain on the reduction of inflammation in elderly people with rheumatoid arthritis in Nursing Homes Medan Medan Bakti Guna Foundation 2018. Suggestions from this study are expected to increase knowledge about the effect of pineapple bromelain on reducing pain due to inflammation of rheumatoid arthritis in the elderly, and can be used as an alternative medicine to reduce rheumatoid arthritis pain.